Licensed firearm dealers, legal compliance, and local homicide: a case study - Stansfield, Richard (Criminology & public policy, 2023)
Research summary This study uses a combination of tract-level and street network-level analyses to examine: (1) the overall association between federally licensed firearm dealers (FFLs) and homicides, (2) the relationship between dealers with serious violations (such as selling to prohibited buyers or failing to record sales) and homicide, and (3) whether the dealer-homicide association is moderated by community disadvantage. Results replicate and confirm a relationship between dealers and homicides in disadvantaged neighborhoods. Importantly, however, we also find that proximity to noncompliant dealers specifically elevates the risk of lethal violence. Policy implications We detail how a coordinated effort between federal, state, and local agencies to regulate firearm dealers and ensure that legal compliance can be instrumental in reducing gun violence. There is a clear need for increased oversight of gun dealers and more robust policies that hold negligent dealers accountable, including the necessary funding and regulatory manpower to enable regular auditing and support consistent follow-up for noncompliant dealers. A comprehensive policy framework that supports supply-side gun violence reduction should include additions to state-level laws that require record keeping, videotaping and store security, and regular inspection for firearm dealers.